Efficacy and safety of intravenous fentanyl administered by ambulance personnel. Issue 4 (27th November 2015) - Friesgaard, K. D.; Nikolajsen, L.; Giebner, M.; Rasmussen, C.‐H.; Riddervold, I. S.; Kirkegaard, H.; Christensen, E. F.
Abstract : Background: Management of pain in the pre‐hospital setting is often inadequate. In 2011, ambulance personnel were authorized to administer intravenous fentanyl in the Central Denmark Region. The aim of this study was to evaluate the efficacy and safety of intravenous fentanyl administered by ambulance personnel. Methods: Pre‐hospital medical charts from 2348 adults treated with intravenous fentanyl by ambulance personnel during a 6‐month period were reviewed. The primary outcome was the change in pain intensity on a numeric rating scale (NRS) from before fentanyl treatment to hospital arrival. Secondary outcomes included the number of patients with reduction in pain intensity during transport (NRS ≥ 2), the number of patients with NRS > 3 at hospital arrival, and potential fentanyl‐related side effects. Results: Fentanyl reduced pain from before treatment (8, IQR 7–9) to hospital arrival (4, IQR 3–6) (NRS reduction: 3, IQR 2–5; P = 0.001), 79.3% of all patients had a reduction in > 2 on the NRS during transport, and 58.4% of patients experienced pain at hospital arrival (NRS > 3). Twenty‐one patients (0.9%) had oxygen saturation < 90%. A decrease in Glasgow Coma Scale was seen in 31 patients (1.3%) and hypotension observed in 71 patients (3.0%). Conclusion: Intravenous fentanyl caused clinically meaningful pain reduction in most patients and was safe in the hands of ambulance personnel. Many patients had moderate to severe pain at hospital arrival. As the protocol allowed higher doses of fentanyl, feedback on effect and safety should be part of continuous education of ambulance personnel.